The Gender Citation Gap in Undergraduate Student Research: Evidence from the Political Science Classroom. Issue 4 (1st October 2020) - Liu, Li-Yin; Devine, Christopher J.; Gauder, Heidi
ABSTRACT: Previous studies documented a "gender citation gap" in political science whereby women are less likely to be cited in published research and course syllabi, especially by male scholars. However, no previous study examined citation patterns among students in political science courses to determine if similar patterns are evident in their research. This article analyzes an original database of individual as well as group research assignments from an undergraduate research methods course. Our analysis indicates that male students are significantly less likely than female students to cite research published by women—whether as first authors, any of the authors, or the average percentage of authors per team. However, in a subsequent group research assignment, gender diversity had no discernible effect on group citation patterns. We discuss the implications of these findings for current pedagogical practices and the future state of the discipline.